Application of Fuzzy Time Series Cheng in Forecasting Bukittinggi's Consumer Price Index - Afifah Nabilah; Fadhilah Fitri; Yenni Kurniawati (UNP Journal of Statistics and Data Science, 2026)
The Consumer Price Index (CPI) is one of the main indicators used to measure inflation and assess the public’s purchasing power. Based on CPI monitoring in March 2025, Bukittinggi City recorded the highest year-on-year (y-o-y) inflation rate in West Sumatra at 0.50 percent, with a CPI of 106.99. This indicates significant price fluctuations, which require careful analysis and forecasting to support regional economic policymaking. This study aims to forecast the CPI of Bukittinggi City for April 2025 using the Fuzzy Time Series (FTS) Cheng method. The data used consists of monthly CPI values from January 2020 to March 2025, totaling 63 observations, obtained from the official website of Statistics Indonesia (BPS). The forecasting result using the FTS Cheng method for April 2025 shows a CPI value of 106.19. To evaluate the model's accuracy, the Mean Absolute Percentage Error (MAPE) and Mean Absolute Error (MAE) were employed, yielding values of 0.82% and 0.90%, respectively. These values fall into the “very good” category based on standard forecasting accuracy criteria. The FTS Cheng method was selected due to its ability to accommodate data fluctuations and provide weighted relationships between fuzzy intervals, thus enhancing forecasting accuracy in dynamic economic conditions. However, this study is limited to univariate data and does not compare the FTS Cheng method with other forecasting models. This research provides valuable insights for local governments in designing effective economic strategies based on reliable predictive models.